Emetophobia (specific phobia of vomiting): Its Relationship with Anxiety-related Disorders and Cognitive Behavioral Therapeutic Approach - Vahdet Gormez; Yavuz Meral; Abdurrahman Cahid Orengul (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Emetophobia (specific phobia of vomiting) emerges as one of the most neglected clinical conditions in clinical practice and academic literature. In this article, a phenomenological, epidemiologic and clinical picture of emetophobia is presented and the cognitive behavioral model is discussed as a therapeutic approach for its treatment [JCBPR 2017; 6(1.000): 39-48]